Quality of worklife and organizational commitment: Government accountants in Malaysia - Mohd Hanefah, Mustafa; Md Zain, Ali Yusob; Ismail, Hamzah; Mat Zin, Razali (2000)
This study was conducted to examine the nature iof relationships between the perceived presence of quality of worklife (QWL)factors and organizational commitment using samples from government accountants in Malaysia. Accountants in government sector were selected to participate in this study.A total of 145 sets of questionnaires were sent to the organization, and 74 usable questionnaires representing a response rate of 51.4% were used for statistical analysis. A QWL measure consisting of seven factors: growth and development, participation, physical environment, supervision, pay and benefit, social relevance, and workplace integration was developed based on Walton's (1974) conception.The three component model and measure of organizational commitment developed by Allen and Meyer (1990) was adopted in this study. Results of regression analyses indicated that only two QWL factors, growth and development and pay and benefit, were significant in explaining organizational commitment, Implication and suggestions for further research are also discussed.